Hetero-epitaxially anchoring Au nanoparticles onto ZnO nanowires for CO oxidation. Issue 83 (4th September 2015) - Liu, Jiaxin; Qiao, Botao; Song, Yian; Huang, Yudong; Liu, Jingyue (Jimmy)
Abstract : Epitaxiallyanchoring gold nanoparticles for better catalysis. Abstract : Supported Au nanoparticles (NPs) sinter easily. Anchoring Au NPs is of fundamental interest and practical importance. We stabilized Au NPs by growing them hetero-epitaxially into the facets of ZnO nanowires. The sintering of epitaxially anchored Au NPs was significantly reduced at high calcination temperatures and during CO oxidation.